2017
DOI: 10.1186/s40813-017-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival of porcine epidemic diarrhea virus (PEDV) in thermally treated feed ingredients and on surfaces

Abstract: BackgroundInfection with Porcine Epidemic Diarrhea Virus (PEDV) causes vomiting, diarrhea, and dehydration in young pigs. The virus made its first appearance in the U.S. in 2013, where it caused substantial neonatal mortality and economic losses in the U.S. pork industry. Based on outbreak investigations, it is hypothesized that the virus could be transmitted through contaminated feed or contaminated feed surfaces. This potential risk created a demand for research on the inactivation kinetics of PEDV in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Collectively, the findings indicate that none of the source ingredients nor the outgoing feed at the feed mills sampled were positive for viral RNA, suggesting the non-animal origin ingredients and feed were not contaminated with PEDV or PDCoV. However, experimental studies by Trudeau et al (33, 34) did show that feed ingredients, soybean meal in particular, spiked with PEDV, PDCoV, and TGEV in a laboratory setting could maintain live virus for a period of time at room temperature. The authors also found that different ingredients supported different virus survival periods which they believe may be due to differences in moisture content, ether content and/or pH of each ingredient.…”
Section: Literature Review Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Collectively, the findings indicate that none of the source ingredients nor the outgoing feed at the feed mills sampled were positive for viral RNA, suggesting the non-animal origin ingredients and feed were not contaminated with PEDV or PDCoV. However, experimental studies by Trudeau et al (33, 34) did show that feed ingredients, soybean meal in particular, spiked with PEDV, PDCoV, and TGEV in a laboratory setting could maintain live virus for a period of time at room temperature. The authors also found that different ingredients supported different virus survival periods which they believe may be due to differences in moisture content, ether content and/or pH of each ingredient.…”
Section: Literature Review Resultsmentioning
confidence: 92%
“…Trudeau et al (33, 34) conducted experimental studies to investigate inactivation kinetics of PEDV, PDCoV, and TGEV in feed and feed ingredient matrices and on solid surfaces. Feed and non-animal origin feed ingredients used in these studies included complete feed, corn, soybean meal, corn dried distillers grains with solubles, and vitamin and trace mineral premix.…”
Section: Literature Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Original research (Dee, Clement, et al, ; Dee, Neill, Clement, Christopher‐Hennings, & Nelson, ; Dee et al, ) and recent review papers (Gordon et al, ; Jones, Woodworth, Dritz, & Paulk, ; USDA APHIS, ) have begun to identify and assess the risk of feed and non‐animal feed ingredient as potential fomites for spreading virus. For example, PEDV has been shown to survive for extended periods of time on conventional and specialty soybean meal (Dee et al, , ; Trudeau, Verma, Sampedro, et al, ; Trudeau, Verma, Uriolla, et al, ). Current biosecurity protocols for sourcing, transport and receiving bulk feed ingredients have been enhanced relative to those in place prior to the introduction of PEDV into North America (AFIA, ; ANAC, ; National Pork Board, ).…”
Section: Retrospective Review Of Epidemiology From 2014 Canadian Pedvmentioning
confidence: 99%
“…Independent trials demonstrate that, depending on storage temperatures, PEDV inoculated on SDAP does not survive over 1–3 weeks (Dee et al, ; Pujols & Segalés, ; Trudeau, Verma, Uriolla, et al, ). The SDPP investigated by CFIA was produced over 10 weeks before the Index case and over 13 weeks before CFIA collected their sample (NASDBPP, ).…”
Section: Retrospective Review Of Epidemiology From 2014 Canadian Pedvmentioning
confidence: 99%